Rekayasa Antarmuka ETL dan HTM Bebas Dopan untuk Sel Surya Perovskit Efisien dan Stabil - Alifqi, Syeva Arsya Wahyu; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2026)
Perovskite solar cells (PSCs) have demonstrated remarkable power conversion efficiencies (PCEs), yet their path to commercialization is critically hindered by significant non-radiative recombination losses and long-term operational instability. These degradation pathways and efficiency losses are predominantly located at the interfaces between the perovskite absorber and the charge transport layers (ETL and HTM). The state-of-the-art often relies on high-temperature processed TiO₂ as the ETL and the expensive, hygroscopic dopant-reliant Spiro-OMeTAD as the HTM, which themselves are primary sources of instability. The research gap is the urgent need for stable, low-cost, and particularly dopant-free interfacial materials that can be processed at low temperatures. This literature review synthesizes and analyzes recent progress in interface engineering, focusing on low-temperature ETL alternatives (e.g., fullerene derivatives and ZnO) and the development of high-performance dopant-free HTMs. We conclude that replacing the problematic Spiro-OMeTAD with stable, dopant-free alternatives, such as the polymer P3HT or robust inorganic materials like NiOₓ and CuGaO₂, is the most critical and effective strategy for realizing efficient, stable, and commercially viable perovskite photovoltaics.